Molecular characterisation of Eimeria tenella porin, a potential anticoccidial drug target - Lee, Xin-Wei; Lam, Su Datt; Mohd Firdaus-Raih,; Wan, Kiew-Lian (Penerbit Universiti Kebangsaan Malaysia, 2020)
Eimeria tenella is an apicomplexan parasite that causes the economically important disease coccidiosis in chickens. An estimated loss over $3 billion USD per annum has been reported. Control of coccidiosis relies on chemotherapy and vaccination but drug resistance is common and live vaccines are relatively expensive. Therefore, there is an urgent need to develop new drugs to control Eimeria infections. Recent studies have shown that the pore forming structures of porin play important roles in many eukaryotic organisms. In this study, we have generated and characterised a putative porin cDNA sequence from E. tenella that we have named Etporin. Sequence alignments showed that Etporin is 47 % similar to the putative porin sequence of Toxoplasma gondii, while a search against the Conserved Domain Database (CDD) shows that Etporin contains the Porin3 superfamily domain. Multiple sequence alignment with porin sequences from various eukaryotic organisms showed that the conserved VKXKX and GLK/STK motifs are present in Etporin. Analysis of the predicted Etporin 3D structure showed a classic beta barrel structure consisting of 19 beta-strands. Taken together, these results suggested Etporin has the potential to be developed into an anticoccidial drug target.